2013
DOI: 10.1371/journal.pone.0078262
|View full text |Cite
|
Sign up to set email alerts
|

Zonation of Nitrogen and Glucose Metabolism Gene Expression upon Acute Liver Damage in Mouse

Abstract: Zonation of metabolic activities within specific structures and cell types is a phenomenon of liver organization and ensures complementarity of variant liver functions like protein production, glucose homeostasis and detoxification. To analyze damage and regeneration of liver tissue in response to a toxic agent, expression of liver specific enzymes was analyzed by in situ hybridization in mouse over a 6 days time course following carbon tetrachloride (CCl4) injection. CCl4 mixed with mineral oil was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 34 publications
(39 reference statements)
3
37
0
Order By: Relevance
“…It is reported that, hepatic IGF-I acted directly on the hepatocytes in a GH-independent manner, regulated hepatocytes cell proliferation, differentiation and metabolism (Takahashi., 2012;Pivonello et al, 2014). Present observation agree with this, KDF treatment did not change the level of HDL, LDL, TC, TG and BG, but it dramatically increased the mRNA expressions of PCK, G6PC, and FBPase in liver, which are the key regulatory enzymes for hepatic gluconeogenesis (Ghafoory et al, 2013). In liver, PCK catalyzes the first committed step in gluconeogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…It is reported that, hepatic IGF-I acted directly on the hepatocytes in a GH-independent manner, regulated hepatocytes cell proliferation, differentiation and metabolism (Takahashi., 2012;Pivonello et al, 2014). Present observation agree with this, KDF treatment did not change the level of HDL, LDL, TC, TG and BG, but it dramatically increased the mRNA expressions of PCK, G6PC, and FBPase in liver, which are the key regulatory enzymes for hepatic gluconeogenesis (Ghafoory et al, 2013). In liver, PCK catalyzes the first committed step in gluconeogenesis.…”
Section: Discussionsupporting
confidence: 87%
“…). The local effect of CCl 4 is due to the zonated expression of CYP2E1, the major P450 cytochrome that metabolizes CCl 4 . In order to determine whether Wnt signaling is activated following acute CCl 4 injury, we conducted in situ hybridization for the Wnt target gene, Axin2 .…”
Section: Resultsmentioning
confidence: 99%
“…CCl4 injury leads to centrilobular necrosis within 48 hours of CCl4 administration (Supplemental Figure 1). The local effect of CCl4 is due to the zonated expression of CYP2E1, the major P450 cytochrome that metabolizes CCl4 (28). In order to determine whether Wnt signaling is activated following acute CCl4 injury, we conducted in situ hybridization for the Wnt target gene, Axin2 (19,29).…”
Section: Injury Induces De Novo Wnt Response In Mid-lobular Hepatocytesmentioning
confidence: 99%